Inovasi Produk Perbankan Syariah Di Indonesia Dalam Menghadapi Tantangan Ekonomi Digital Dan Perubahan Kebutuhan Konsumen - Nur Sitorus, Siti Ghadizah; Santri, Nur (Universitas Pahlawan Tuanku Tambusai, 2025)
Digital transformation presents both challenges and opportunities for Islamic banking in Indonesia to meet the needs of modern consumers while adhering to Sharia principles. This study employs a qualitative approach through library research to analyze product innovation strategies in Islamic banking amidst the challenges of the digital economy. Data were analyzed using content analysis techniques from various relevant literature. The findings indicate that adopting digital technologies such as mobile banking, blockchain, and artificial intelligence (AI) enhances efficiency, accessibility, and customer trust. Product diversification, including Hajj savings and waqf-based investments, also plays a crucial role in attracting modern consumers. However, limitations in technological infrastructure, resistance to change, and low financial literacy in Sharia banking pose significant obstacles. To address these issues, collaboration with fintech, regulatory strengthening, and investment in human resource development are recommended. These measures are expected to support financial inclusion, enhance competitiveness, and strengthen the contribution of Islamic banking to Indonesia's digital economy.